Westonci.ca connects you with experts who provide insightful answers to your questions. Join us today and start learning! Get immediate and reliable answers to your questions from a community of experienced professionals on our platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
To convert the quadratic equation [tex]\( y = x^2 - 14x + 52 \)[/tex] into its vertex form, we first need to identify the vertex [tex]\((h, k)\)[/tex].
The general form of a quadratic equation is:
[tex]\[ y = ax^2 + bx + c \][/tex]
The vertex form of a quadratic equation is:
[tex]\[ y = a(x - h)^2 + k \][/tex]
where [tex]\((h, k)\)[/tex] is the vertex of the parabola. The formula to find the vertex [tex]\( (h, k) \)[/tex] is:
[tex]\[ h = -\frac{b}{2a} \][/tex]
[tex]\[ k = c - \frac{b^2}{4a} \][/tex]
For the given equation [tex]\( y = x^2 - 14x + 52 \)[/tex]:
- The coefficient [tex]\( a \)[/tex] is 1
- The coefficient [tex]\( b \)[/tex] is -14
- The constant term [tex]\( c \)[/tex] is 52
Calculate [tex]\( h \)[/tex]:
[tex]\[ h = -\frac{b}{2a} = -\frac{-14}{2 \cdot 1} = \frac{14}{2} = 7 \][/tex]
Calculate [tex]\( k \)[/tex]:
[tex]\[ k = c - \frac{b^2}{4a} = 52 - \frac{(-14)^2}{4 \cdot 1} = 52 - \frac{196}{4} = 52 - 49 = 3 \][/tex]
Thus, the vertex [tex]\((h, k)\)[/tex] is [tex]\((7, 3)\)[/tex].
Therefore, the vertex form of the quadratic equation is:
[tex]\[ y = 1(x - 7)^2 + 3 \][/tex]
So, the correct answer is:
[tex]\[ y = (x - 7)^2 + 3 \][/tex]
The general form of a quadratic equation is:
[tex]\[ y = ax^2 + bx + c \][/tex]
The vertex form of a quadratic equation is:
[tex]\[ y = a(x - h)^2 + k \][/tex]
where [tex]\((h, k)\)[/tex] is the vertex of the parabola. The formula to find the vertex [tex]\( (h, k) \)[/tex] is:
[tex]\[ h = -\frac{b}{2a} \][/tex]
[tex]\[ k = c - \frac{b^2}{4a} \][/tex]
For the given equation [tex]\( y = x^2 - 14x + 52 \)[/tex]:
- The coefficient [tex]\( a \)[/tex] is 1
- The coefficient [tex]\( b \)[/tex] is -14
- The constant term [tex]\( c \)[/tex] is 52
Calculate [tex]\( h \)[/tex]:
[tex]\[ h = -\frac{b}{2a} = -\frac{-14}{2 \cdot 1} = \frac{14}{2} = 7 \][/tex]
Calculate [tex]\( k \)[/tex]:
[tex]\[ k = c - \frac{b^2}{4a} = 52 - \frac{(-14)^2}{4 \cdot 1} = 52 - \frac{196}{4} = 52 - 49 = 3 \][/tex]
Thus, the vertex [tex]\((h, k)\)[/tex] is [tex]\((7, 3)\)[/tex].
Therefore, the vertex form of the quadratic equation is:
[tex]\[ y = 1(x - 7)^2 + 3 \][/tex]
So, the correct answer is:
[tex]\[ y = (x - 7)^2 + 3 \][/tex]
Thank you for choosing our service. We're dedicated to providing the best answers for all your questions. Visit us again. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.